Book review:E.JUHASZ (Hsgb.), Byzanz und das Abendland V, Budapest 2018 - ΑΝΤΩΝΟΠΟΥΛΟΣ Παναγιώτης Γ. (Byzantina Symmeikta, 2019)
Book review:E.Juhasz (Hsgb.), Byzanz und das Abendland V, Budapest 2018